A proposed wave farm on the Galician coast. (15th July 2015) - Veigas, M.; López, M.; Romillo, P.; Carballo, R.; Castro, A.; Iglesias, G.
Highlights: The productions of four wave energy converters are estimated and compared. The electric production of single units and 12 MW power plants are considered. Three study sites at different water depths in the northwest of Spain are studied. The occupation of the wave plant is considered to determine the best technology. The Wave Dragon resulted the technology with the highest production. Abstract: This work is focused on the analysis of the wave resource and its exploitation by means of a proposed 12 MW wave plant in Northwestern Spain. For this purpose, a total of four current technologies of wave conversion are analysed at three different sites located at different water depths, which correspond to one of the European areas with the greatest wave energy resource and where its electric production is still underdeveloped. To carry out the research, the wave data recorded at an offshore buoy near the area and the power matrices of the four selected wave energy technologies are used. The offshore wave conditions—representing 95% of the total energy of an average year—are propagated through spectral numerical modelling towards the coast. On the basis of the results, two of the four selected technologies forming the 12 MW power plants and one of the three considered points emerge as the ones allowing the greatest energy production and, at the same time, having a minimum area of occupation which, in turn, is crucial to reducing the visual impact. Finally, this research discusses the energy supply capacity of the proposed plants to satisfy the energy consumption required by nearby communities.